Agent-Based Simulation for Evaluating the Effect of Different Walking and Driving Speed on Disaster Evacuation in Aceh - Sinung Widiyanto; Dimas Adi; Nadhila Nurdin; Fadila Fadila (IPTEK The Journal of Engineering, 2021)
Agent-Based Modeling and Simulation (ABMS) was implemented to build and develop an evacuation simulation model. In this research, ABMS is simulated in several evacuation scenarios with an output: the evacuation rate of two different decision choice evacuation modes (walking or driving to the evacuation points). The result of this tsunami evacuation simulation shows that the decision choices on the evacuation mode are highly correlated to the evacuation rate. Observed in the simulation that there is a typical choice that leads to the higher evacuation rate, the choice is by maximizing the pedestrian agents on the population distribution.